Student Problem Solving Analysis by Step John Dewey Reviewed from Learning Style - Ni Ummu Kulsum; Kristayulita Kristayulita (IJECA (International Journal of Education and Curriculum Application), 2019)
This research aims to describe the student’s mathematical problem solving based on John Dewey’s step viewed by learning style. The subjects are 2 students with a visual learning style, 2 students with auditory learning style, and a student with kinaesthetic learning. The data was collected through a questionnaire of learning style, the test of mathematics problem solving, interview, and documentation. Then it was analyzed used Milles and Huberman model’s data analyzed technique consist of data reduction, data display, and conclusion (verification). This research shows that: (1) the visual subject confronted the problem by reading the question silently in several times, the subject can’t define the problem correctly, can’t found the right solution so that calculating and the answer is not correct, and can’t test consequences (looking back), (2) the auditory subject confronted the problem with reading the question in several times loudly, the subject can define the problem correctly, can found the right solution so that calculating and the answer correctly, and can’t test consequences (looking back), (3) the kinesthetic subject confronted the problem with reading the question in several times, the subject can’t define the problem correctly, can’t found the right solution so that calculating and the answer is not correct, and can’t test consequences (looking back).